Production risk and adoption of irrigation technology: Evidence from small-scale farmers in Chile - César Salazar; John Rand (Latin American Economic Review, 2016)
In most developing countries non-irrigation status often dominates adoption of traditional and modern irrigation technology. In this paper, we study the effect of production risk on irrigation technology choice among small-scale farmers in Chile, applying sample selection and discrete choice models. We find that more educated farmers, with credit access, receiving extension services, and living in communes with more adopters are more likely to use modern irrigation techniques. Moreover, production risk is often associated with adoption of traditional irrigation, and this risk often undermines a shift to more modern irrigation systems. Controlling for pre-conditions that determine irrigation choices clearly improves our understanding of small-scale farmer irrigation adoption decisions and we argue that weaker knowledge about and lower automatic diffusion of modern irrigation is a main obstacle for improving small-scale farmer productivity.
Keywords: D8; O13; Q15; Q55; 330; Production risk; Irrigation; Technology adoption